Implementasi pendekatan STEAM Berbasis PJBL Pada Materi Pencemaran Lingkungan untuk Meningkatkan Keterampilan Kolaborasi Siswa Kelas VII Negeri 3 Gorontalo - Sri Wirdayanti Andup; Elya Nusantari; Hartono Mamu (Jurnal Penelitian Pendidikan IPA, 2025)
This research to investgate the implimentation of the STEAM (science, technology, engineering, art and mathematic) approach base on Prjocet Based Learning (PJBL) in enviromental pollution content to enchance students colllaboration skills. The research utilizes the Pre-Experimental Design method. This type of research involves a single group of subjects receiving treatment without a control group. The research design employed is the One-Shot Case Study. Data collection techniques include documentation and non-test methodss. The population comprises all 7th grade classes, with the sample specifically taken from the VII D class. Results obtained from categorization analysis for self-assessment and peer assessment is more dominant in the medium category, this shows that self-assessment and peer assessment is not optimal. Self-assessment (self-assessment) and peer assessment of skills Student collaboration is included in the medium category because of variations in learning perception and assessment of each individual. The result from the VII D indicates in increase in collaboration skills which obtains score 82, 32 on average in meeting and 86,07 in meeting III and they are included in very good criteria. In conlusion, the STEAM approach based on Project Based Learning (PJBL) is effective in enhancing student’s collaboration skills in the context of enviromental pollution.